AUXIN RESPONSE FACTOR17 Directly Regulates MYB108 for Anther Dehiscence. Issue 2 (25th July 2019) - Xu, Xiao-Feng; Wang, Bo; Feng, Yi-Feng; Xue, Jing-Shi; Qian, Xue-Xue; Liu, Si-Qi; Zhou, Jie; Yu, Ya-Hui; Yang, Nai-Yin; Xu, Ping; Yang, Zhong-Nan
Abstract : ARF17-MYB108 defines a pathway for auxin to regulate anther dehiscence in Arabidopsis. Abstract: The timely release of mature pollen following anther dehiscence is essential for reproduction in flowering plants. AUXIN RESPONSE FACTOR17 (ARF17) plays a crucial role in pollen wall pattern formation, tapetum development, and auxin signal transduction in anthers. Here, we showed that ARF17 is also involved in anther dehiscence. The Arabidopsis ( Arabidopsis thaliana ) arf17 mutant exhibits defective endothecium lignification, which leads to defects in anther dehiscence. The expression of MYB108, which encodes a transcription factor important for anther dehiscence, was dramatically down-regulated in the flower buds of arf17 . Chromatin immunoprecipitation assays and electrophoretic mobility shift assays showed ARF17 directly binds to the MYB108 promoter. In an ARF17-GFP transgenic line, in which ARF17-GFP fully complements the arf17 phenotype, ARF17-GFP was observed in the endothecia at anther stage 11. The GUS signal driven by the MYB108 promoter was also detected in endothecia at late anther stages in transgenic plants expressing promoterMYB108::GUS . Thus, the expression pattern of both ARF17 and MYB108 is consistent with the function of these genes in anther dehiscence. Furthermore, the expression of MYB108 driven by the ARF17 promoter successfully restored the defects in anther dehiscence of arf17 . These results demonstrated that ARF17 regulates the expression of MYB108 for anther dehiscence. Together with its function in microcytes and tapeta, ARF17 likely coordinates the development of different sporophytic cell layers in anthers. The ARF17-MYB108 pathway involved in regulating anther dehiscence is also discussed.